Genome sequence of the broad-host-range Pseudomonas phage Phi-S1 - Sillankorva, Sanna (2012)
The broad-host-range lytic Pseudomonas phage Φ-S1 possess a 40,192 bp double-stranded DNA (dsDNA) genome of 47 open reading frames (ORFs) and belongs to the family Podoviridae, subfamily Autographivirinae, genus T7likevirus.